Topicilazation and Focalization in Persian - Rezai, Vali; Youhanaee, Manijeh; Ghasemi, Hasan (Richtmann Publishing, 2012)
This article provides a syntactic analysis of Topicalization and Focalization processes in Persian within the frameworkof minimalist syntax. According to Haegeman and Gueron’s Split CP Hypothesis (1999), Topicalization is a recursive processand can apply to more than one constituent in a sentence, while Focalization is unique and therefore appears in a singleprojection. In this paper we argue that in Persian more than one constituent might undergo focalization. This implies thatFocalization cannot be unique. Thus, we first propose two Focal Phrases in the periphery position of a clause. The specifierpositions of the two Focal phrases are the landing sites of the focused constituents. Then we suggest the relative position offocal phrases with topic phrases in Persian. It will be concluded that the first focus phrase appears immediately after thecomplementizer phrase before the first recursive topic phrase followed by the second focus phrase and recursive topic phraserespectively.